2021
DOI: 10.7206/cemj.2658-0845.59
|View full text |Cite
|
Sign up to set email alerts
|

Does Psychic Distance Still Matter? Empirical Evidence from Poland

Abstract: Objective: The objective of the article is to fill a research gap regarding the impact of psychic distance on the initiation of relationships by managers from Poland-based firms and to analyze the psychic distance’s influence on firm performance. Research methodology: The article is based on quantitative research conducted among managers from 201 Poland-based companies operating in foreign markets. The study used a structured questionnaire consisting mainly of closed questions. The dataset contained companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For instance, Bodlaj et al (2020) measured to how many foreign regional markets firms exported their products, Annushkina (2014) and Götz and Jankowska (2019) counted in how many continents firms were active, while Nowiński and Rialp (2013) and Roolaht (2017) considered having activities on several continents and in a large number of countries as a sign of success. Fonfara et al (2021) and Panibratov and Klishevich (2020) agreed that successful firms operated in psychically distant markets. The number of foreign export markets was also an important indicator for Ferencikova and Hluskova (2015) and Zemplinerová (2012) while Filippov (2011) and Sass and Vlčková (2019) emphasized that successful firms had foreign affiliates in a large number of foreign countries.…”
Section: Understandings Of Central and Eastern European Firms’ Intern...mentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, Bodlaj et al (2020) measured to how many foreign regional markets firms exported their products, Annushkina (2014) and Götz and Jankowska (2019) counted in how many continents firms were active, while Nowiński and Rialp (2013) and Roolaht (2017) considered having activities on several continents and in a large number of countries as a sign of success. Fonfara et al (2021) and Panibratov and Klishevich (2020) agreed that successful firms operated in psychically distant markets. The number of foreign export markets was also an important indicator for Ferencikova and Hluskova (2015) and Zemplinerová (2012) while Filippov (2011) and Sass and Vlčková (2019) emphasized that successful firms had foreign affiliates in a large number of foreign countries.…”
Section: Understandings Of Central and Eastern European Firms’ Intern...mentioning
confidence: 97%
“…In addition, some authors have used or suggested using a combination of several objective and/or perceptual/subjective measures . For instance, Fonfara et al (2021) measured performance by calculating an arithmetic average of each firm’s market share, sales, profit and return on investment compared to closest competitors. Stocker and Várkonyi (2022) used an index consisting of several objective and subjective measures representing firms’ adaptivity and operationality.…”
Section: Understandings Of Central and Eastern European Firms’ Intern...mentioning
confidence: 99%
See 1 more Smart Citation